2012
DOI: 10.1257/aer.102.7.3333
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Time Preferences from Convex Budgets

Abstract: Experimentally elicited discount rates are frequently higher than what one would infer from market interest rates and seem unreasonable for economic decision-making. Such high rates have often been attributed to dynamic inconsistency, as in present bias and hyperbolic discounting. A commonly recognized bias of standard elicitation techniques is the use of linear preferences for identification. We present a novel methodology for identifying time preferences, both discounting and utility function curvature, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
178
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(189 citation statements)
references
References 37 publications
11
178
0
Order By: Relevance
“…More specifically, the decay in effort is exponential, not hyperbolic, in the delay. This finding is consistent with the evidence of non-present bias on monetary payments (Andreoni and Sprenger, 2012), as opposed to real effort (DellaVigna and Pope, 2017). …”
Section: The Discount Functions Fitting Illness or Addiction Procesupporting
confidence: 89%
“…More specifically, the decay in effort is exponential, not hyperbolic, in the delay. This finding is consistent with the evidence of non-present bias on monetary payments (Andreoni and Sprenger, 2012), as opposed to real effort (DellaVigna and Pope, 2017). …”
Section: The Discount Functions Fitting Illness or Addiction Procesupporting
confidence: 89%
“…In their experiments they showed that it is essential to have one risk preference elicitation task for measuring the curvature of the utility function, another task to identify the discount rate conditional on knowing the utility function, and then jointly estimate the structural model defined over the parameters of the utility function and discount rate. More recently, Andreoni and Sprenger (2012) extended the methodology proposed by Andersen et al (2008) by developing a procedure they called the Convex Time Budget (CTB) method that does not require a separate risk aversion task to identify the curvature of the utility function. The procedure involves giving the subject…”
Section: Discussionmentioning
confidence: 99%
“…If one decides not to use a FED, then extra care is needed in order to equalize transaction costs across all time periods, including physical costs. Andreoni and Sprenger (2012) describe six specific measures to equate transaction costs and ensure payment reliability.…”
Section: Possible Improvements To Time Preference Elicitation Methodsmentioning
confidence: 99%
“…In the monetary intertemporal choice task, a variant of Andreoni and Sprenger (2012)’s Convex Time Budget (CTB), participants were asked to allocate an experimental budget of $500 into two payments with pre-specified dates, the second of which included interest. Participants had to make 12 of these choices in which the experimental interest rate varied (0%, 0.5%, 1%, or 3%), as did the mailing date of the first payment (either today or four weeks from now) and the time delay between the two payments (four weeks or eight weeks).…”
Section: Methodsmentioning
confidence: 99%